Numerical Simulation of Tunneling Current in an Anisotropic Metal-Oxide-Semiconductor Capacitor - Fatimah A. Noor; Ferry Iskandar; Mikrajuddin Abdullah; Khairurrijal Khairurrijal (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
In this paper, we have developed a model of the tunneling current through a high- dielectric stack in MOS capacitors with anisotropic masses. The transmittance was numerically calculated by employing a transfer matrix method and including longitudinal-transverse kinetic energy coupling which is represented by an electron phase velocity in the gate. The transmittance was then applied to calculate tunneling currents in TiN/HfSiOxN/SiO2/p-Si MOS capacitors. The calculated results show that as the gate electron velocity increases, the transmittance decreases and therefore the tunneling current reduces. The tunneling current becomes lower as the equivalent oxide thickness (EOT) of HfSiOxN layer increases. When the incident electron passed through the barriers in the normal incident to the interface, the electron tunneling process becomes easier. It was also shown that the tunneling current was independent of the substrate orientation. Moreover, the model could be used in designing high speed MOS devices with low tunneling currents.